Projeto conceitual de uma planta de produção de metanol a partir da gaseificação de biomassa - Pereira, Geisiane Rodrigues (2024)
In the face of growing energy demand and environmental issues, renewable energy sources are becoming increasingly necessary. Biomass stands out as a viable alternative, with gasification being one of the energy utilization methods with great potential. It is a thermal conversion process in which compounds are partially oxidized, generating syngas, which is primarily composed of: CH4, CO, CO2, and H2. The application of syngas depends on its composition, which in turn is influenced by variables such as temperature, equivalence ratio, gasification agent, and other operational parameters. Due to its complexity, it can be preliminarily studied through modeling, a tool that helps predict the behavior of the gasifier. The objective of this work was to construct a gasification reaction block in the AVEVATM Process Simulation. The process modeling used a thermodynamic stoichiometric equilibrium approach, and experimental data extracted from the literature were used to validate the results. The biomasses studied were rubber tree wood, hardwood, two types of wood chips, and sawdust pellets. Three gasifier models were developed, employing the equilibrium constant equations for the reactions that occur in the reduction zone. One of the models used empirical models to predict the composition of the syngas. The process variables studied were gasification temperature and equivalence ratio (ER). The syngas composition obtained through Model 1 for rubber tree wood gasification, with ER=0.33 and Moisture=18.5, was: 17.72% CO, 18.88% H2, 11.93% CO2, 0.55% CH4, and 50.91% N2, with a mean squared error of 1.56, demonstrating the applicability of the model for process description. Two flow diagrams (Plant 1 and Plant 2) were developed for methanol production using the gasification product. The plant is conceptually designed to process biomass at a rate of 100 kmol/h (approximately 59.6 tons per day), and the gasifier operates isothermally at 900°C and 1 atm. The simulation of Plant 1 using wood chips showed a loss of USD 635,820, while Plant 2, processing the same biomass, showed a profit of USD 1,460,907.7.